Beneficial properties of Drimia numidica leaf methanolic extract against the cytogenotoxic effects of mitomycin C on human lymphocytes. (March 2023) - Dormousoglou, Margarita; Boti, Vasiliki; Hela, Dimitra; Vlastos, Dimitris; Antonopoulou, Maria; Chondrogiannis, Christos; Petropoulou, Yiola; Dailianis, Stefanos
Abstract: This study investigated the phytochemical profile of Drimia numidica leaf methanolic extract, as well as its cyto-genotoxic and cyto/genoprotective potential against mitomycin C (MMC) mediated effects on healthy human lymphocytes. Photosynthetic pigments, trace elements, and secondary metabolites were estimated and/or identified in methanolic extract of mature leaves, and the latter was further used for assessing its in vitro biological effects on MMC-free and/or MMC-treated human lymphocytes (at low, non-toxic concentrations of 0.001 and 0.01% v/v). The results showed that D. numidica leaf methanolic extract, being rich in carotenoids, phenolics, flavonoids, organic acids and bufadienolides, could be protective against MMC mediated cyto/genotoxic potential in healthy human lymphocytes. Biomolecules possessing antioxidant and antitumor potential, such as beta-carotene and lutein among others, chlorogenic acid, caffeic acid and their derivatives, minerals such as Si, as well as apigenin- and luteolin-derived glycosides, either individual or in a mixture, could be beneficial rather than harmful, at least at the extract concentrations tested. Although further in vitro and in vivo studies are still needed for elucidating the beneficial (individual and/or additive/synergistic) role of those compounds, the results of the present study are quite promising, thus encouraging new challenges for the appropriate utilization of D. numidica leaf extract. Highlights: The biological properties of Drimia numidica leaf methanolic extract were examined. Human lymphocytes, treated with or without mitomycin C, were used. D. numidica leaf methanolic extract was phytochemically analyzed. Extract was no cyto-genotoxic on human lymphocytes at the tested concentrations. Extract was cyto/genoprotective against mitomycin C at the tested concentrations.